The factors affecting employees' job performance among workers in Shah Alam / Noratikah Najwa Shu Arifin - Shu Arifin, Noratikah Najwa (Faculty of Business and Management, 2019)
This study is conduct to investigate the factors of affecting employees' job performance among workers in Shah Alam. After that, this study also shows us the reason why the job performance is really in important towards organizations. Using survey method, 100 questionnaires have been distributed to the workers in Shah Alam especially the employees who have more experience in working. This study is investigating to understand the factors affecting employees' job performance among workers in Shah Alam. We can say that employees play an important asset to organization in order to make sure the organization achieve their goals and objectives. Furthermore, we can see which factors actually giving the big impact towards employees' job performance.